Landing stability during the single-leg drop jump in footballers with hip and/or groin pain - Sritharan, P.; Schache, A. G.; Crossley, K. M.; Scholes, M. J.; Heerey, J. J.; Mentiplay, B. F.; De Oliveira Silva, D.; King, M. G. (Journal of Sports Sciences, 2026)
Early identification of altered movement patterns can guide interventions for young adults with hip and/or groin pain. Characterising dynamic stability during movement tasks is a unique approach to understanding these altered biomechanics associated with hip and/or groin pain. We quantified two measures of stability: Margin of Stability (MoS); and Whole-Body Angular Momentum (WBAM), during the landing period of the single-leg drop jump for 117 young adult football players with hip/groin pain (27 ± 4 years) and 24 asymptomatic controls (27 ± 6 years). Experimental motion data, ground forces and associated centres-of-pressure were input into biomechanical models to calculate segmental and centre-of-mass kinematics, and subsequently, to calculate MoS and WBAM. Symptomatic individuals demonstrated significantly more positive mediolateral MoS during the early braking phase (0-31% of landing). The sagittal-plane WBAM differed significantly between groups near the transition from braking to propulsion (35-51% of landing) and at take-off (98-100% of landing) due to a lag in torso angular momentum. Whilst differences were small, our findings suggest that symptomatic individuals adopted a conservative landing strategy in which regulating mediolateral MoS appeared to be prioritised over sagittal-plane WBAM. Overall, the analysis of dynamic stability provided new insights into altered biomechanics in the presence of joint pain/pathology.